Recycled LiMn2O4 from the spent lithium ion batteries as cathode material for sodium ion batteries: Electrochemical properties, structural evolution and electrode kinetics. (10th October 2019) - Nie, Xue-Jiao; Xi, Xiao-Tong; Yang, Yang; Ning, Qiu-Li; Guo, Jin-Zhi; Wang, Mei-Yi; Gu, Zhen-Yi; Wu, Xing-Long
Abstract: In the extensive application processes of lithium ion batteries (LIBs), a great quantity of spent LIBs is producing, which is harmful to human and the environment if not handled properly. In addition, due to the scarcity of lithium on earth, sodium with relatively high abundance and low cost is expected to replace lithium. Hence, it is an interesting and urgent work of reusing the spent materials from the end-of-life LIBs for designing sodium-ion batteries (SIBs). Herein, an efficient method is proposed to recycle the spent LiMn2 O4 and directly reuse it as the cathode of SIBs. As electrochemical tests show, such recycled LiMn2 O4 delivers excellent Na-storage properties in SIBs. For example, its discharge capacity can gradually increase to 163.2 mAh g −1 over 50 cycles at 100 mA g −1, and the highest reversible capacity is up to 176.3 mAh g −1 at 20 mA g −1 . It is further revealed by combining the electrochemical analyses and ex-situ characterizations that, the continuous increase of capacity during the initial 50 cycles is due to the phase transition of the spinel into layered structure caused by the Li + /Na + (de)insertion. Studies of electrode kinetics indicate the faster ion diffusion in the layered material than the spinel one. This work provides a new strategy to recycle the spent LIBs, i.e., directly reusing the exhausted electrode materials to the next-generation batteries. Graphical abstract: Image 1 Highlights: A simple and efficient method is proposed to recycle the spent LiMn2 O4 . Recycled LiMn2 O4 can be directly used as cathode for sodium ion batteries (SIBs). Recycled LiMn2 O4 delivers excellent electrochemical properties in SIBs. A series of tests reveal the phase evolution process during the initial 50 cycles. Electrode kinetics is analyzed and discussed by the electrochemical studies.